2017
DOI: 10.7717/peerj.4105
|View full text |Cite
|
Sign up to set email alerts
|

Ability to predict repetitions to momentary failure is not perfectly accurate, though improves with resistance training experience

Abstract: ‘Repetitions in Reserve’ (RIR) scales in resistance training (RT) are used to control effort but assume people accurately predict performance a priori (i.e. the number of possible repetitions to momentary failure (MF)). This study examined the ability of trainees with different experience levels to predict number of repetitions to MF. One hundred and forty-one participants underwent a full body RT session involving single sets to MF and were asked to predict the number of repetitions they could complete before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 43 publications
7
64
1
2
Order By: Relevance
“…Hence, RIR scales might be more advantageous in these populations assuming they are able to accurately predict their repetition performance. Though, Hackett et al (2016) concluded that the ability to predict proximity to MF was not impacted by RT experience and Steele et al (2017a), though reporting improvement with experience, still found the most experienced were less than adequately accurate.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Hence, RIR scales might be more advantageous in these populations assuming they are able to accurately predict their repetition performance. Though, Hackett et al (2016) concluded that the ability to predict proximity to MF was not impacted by RT experience and Steele et al (2017a), though reporting improvement with experience, still found the most experienced were less than adequately accurate.…”
Section: Introductionmentioning
confidence: 98%
“…These RIR scales are designed as a way of assessing/controlling effort by participants estimating how many repetitions they can perform before reaching MF. RIR scales have been argued to be a more valid method of representing effort in close proximity to MF when compared to traditional RPE scales or the use of relative demands from a test of strength (i.e % of one repetition maximum [1RM]; Hackett et al, 2012;Helms et al, 2016;Steele, Endres, Fisher, Gentil & Giessing, 2017a). Indeed, traditional RPE scales often result in submaximal ratings even at MF (Steele, Fisher, McKinnon & McKinnon, 2017c).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations